Sexualities in education: a reader - Meiners, Erica R. (Counterpoints: studies in the postmodern theory of education, 2012)
With germinal texts, new writings, and related art, Sexualities in Education: A Reader illuminates a broad scope of analysis and organization. Composed of a framing essay and nine sections edited by established and emerging scholars and addressing critical topics for researchers and students of sexualities and education, the text provides a timely overview of sexualities considered through a variety of educational lenses and theoretical frameworks. Threads woven throughout include visual, literary, and performing arts; youth perspectives; and an emphasis on justice work in education. The volume provides entry points for students and practitioners at a range of levels. Research-based articles, essays, interviews, poetry and ready-to-reproduce visual materials from the Americas, Europe, and Asia are linked to a resource section to facilitate deep learning, on-going investigation, and informed action.